1994
DOI: 10.1116/1.587563
|View full text |Cite
|
Sign up to set email alerts
|

Growth of beryllium doped AlxGa1−xAs/GaAs mirrors for vertical-cavity surface-emitting lasers

Abstract: Articles you may be interested inDifferential surface photovoltage spectroscopy characterization of a 1.3 μm InGaAlAs/InP vertical-cavity surfaceemitting laser structure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…DBR interfaces are parabolically graded to reduce interface electrical resistance. 2 The InGaAsP multi-quantum well ͑MQW͒ active region consists of seven quantum wells ͑QWs͒ at about 1% compressive strain and six straincompensating barriers at about Ϫ0.9% tensile strain. The MQW is sandwiched between InP spacer layers that have been extended by thin GaAs layers on top of each fused mirror to increase the emission wavelength.…”
Section: ͓S0003-6951͑96͒03019-7͔mentioning
confidence: 99%
“…DBR interfaces are parabolically graded to reduce interface electrical resistance. 2 The InGaAsP multi-quantum well ͑MQW͒ active region consists of seven quantum wells ͑QWs͒ at about 1% compressive strain and six straincompensating barriers at about Ϫ0.9% tensile strain. The MQW is sandwiched between InP spacer layers that have been extended by thin GaAs layers on top of each fused mirror to increase the emission wavelength.…”
Section: ͓S0003-6951͑96͒03019-7͔mentioning
confidence: 99%
“…The layer interfaces are parabolically graded to reduce interface electrical resistance. 10 The InGaAsP multi quantum well ͑MQW͒ active region consists of 7 QWs with about 1.0% compressive strain and 6 barriers with about 0.9% tensile strain. It is embedded in InP spacer layers that have been extended by thin GaAs layers on top of each fused mirror to increase the emission wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…Our measurements imply that CBE may be a better growth procedure for this purpose than MOVPE; this is because the layers are produced by using a controlled growth interrupt instead of by doping a layer during growth. It has been shown that 8-doping at the interfaces of heterostructures used as distributed Bragg reflector (DBR) stacks leads to a low series resistance [29]. For these structures the p-type 8-layers have to be in the material with the higher bandgap, that is AlAs (or AlxGal -xAs) when it is combined with GaAs as the second component.…”
Section: Discussionmentioning
confidence: 99%